Nodular fasciitis: a case series unveiling novel and rare gene fusions, including two cases with aggressive clinical behavior - Saoud, Carla; Agaimy, Abbas; Stöhr, Robert; Michal, Michael; Wang, Scott Kuan Wen; Mandavilli, Srinivas; Charville, Gregory W.; Linos, Konstantinos (Virchows Archiv, 2025)
Nodular fasciitis is a benign myofibroblastic tumor characterized by rapid growth and spontaneous regression. While nodular fasciitis is typically an indolent process, rare cases with benign morphologic features have developed metastases. Conversely, nodular fasciitis with malignant histologic features and benign clinical course have also been reported. In this study, we present seven nodular fasciitis cases with novel USP6 gene fusion partners, in addition to two cases with rare fusions that displayed aggressive clinical behavior. The cohort comprised five females and four males with a median age of 36 years (range 13–59). Tumors were located in the forearm (n = 3), thigh (n = 2), and shoulder, abdominal wall, chest wall, and oral cavity (one each), ranging from 1.4 to 24.0 cm in size (median, 2.2 cm). Except for the clinically aggressive cases, patients presented with painless masses of varying onset from days to months. Of the clinically aggressive cases, one patient presented with a slowly growing subfascial thigh/hip mass over nine years, leading to erosion of the femur and pelvis; the other presented with a painful subfascial thigh mass of several months' duration. Histologically, all cases, including the clinically aggressive ones, showed conventional nodular fasciitis features without nuclear pleomorphism or atypical mitotic figures; one case with aggressive clinical behavior exhibited focal infarction-type necrosis. Break-apart FISH analysis using USP6 flanking probes failed to detect USP6 rearrangement in two cases (false negatives) and was inconclusive in one case. Next-generation RNA sequencing identified USP6 fusions in all cases. The clinically aggressive cases showed fusions with COL1A1 (exon 1) and PPP6R3 (exon 1), while novel fusions were identified in the remaining cases including EIF4A1 (exon 1), FILIP1L (exon 2), NF1 (exon 33), OMD (exon 1), PFN1 (exon 1), RLIM (exon 1), and SETD5 (exon 1). Six patients underwent surgical resection; three were managed conservatively, with two experiencing spontaneous tumor resolution. Of the clinically aggressive cases, one patient had progression of the tumor with erosion of the underlying bone, and the second patient developed local recurrence at 14 months and lung metastasis at 19 months, ultimately dying of disease at 22 months. The remaining patients showed no recurrence or metastasis. Our findings expand the spectrum of USP6 gene fusion partners in nodular fasciitis and, for the first time, report cases with conventional morphology exhibiting aggressive behavior, including death. These observations raise the question of whether a subset of deep lesions with conventional nodular fasciitis histology but unusual clinical features, such as large tumor size, represents malignant nodular fasciitis or alternatively a nodular fasciitis-like myofibroblastic sarcoma.
CRIS-Team Scopus Importer:2025-02-21
Keywords: Aggressive behavior; Nodular fasciitis; Novel gene fusions; Rare partners